Describing patients with a duration of sick leave over and under one year in Norway. (January 2015) - Jacobsen, Henrik B.; Bjørngaard, Johan Håkon; Borchgrevink, Petter C.; Woodhouse, Astrid; Fimland, Marius S.; Hara, Karen W.; Stiles, Tore C.
Abstract Objective: This study aimed to describe the somatic, social, psychological, and work-related factors that characterize participants with a duration of sick leave over and under one year. Methods: During 2012, 181 patients on long-term sick leave were consecutively recruited and asked to answer an extensive survey. Several outcomes were reported, addressing work-related factors and somatic, psychological, and social symptoms. In cross-sectional analyses, sick leave duration was dichotomized as > or < one year, based on Norwegian legislation. Linear and logistic regressions were used to estimate population probabilities and means. Results: The estimated prevalence of pain, fatigue, anxiety, and depression was overall high. There was a tendency towards a higher prevalence of fatigue, anxiety, and depression in those with sick leave duration less than one year, with the exception of sleep problems, which was more frequent in the population with longer duration. Relationship with friends, family, co-workers, and the last workplace were worse in the population with longer duration. Conclusions: Cross-sectional analyses indicated that social and work-related problems are more adverse in patients with longer duration of sick leave, while psychological and somatic symptoms appear less adverse. This is one of the first studies quantitatively demonstrating these differences through comprehensive, simultaneously measured self-report questionnaires.